Inteiros gaussianos - Lima, Thaise Oliveira de (2022)
The main objective of this work is to study algebraic properties of some ring of Gaussian integers Z[i]. For example, we will prove that Z[i] is a domain Euclidean and therefore a unique factoring domain. As an application of arithmetic character, characterizing the prime numbers that can be expressed as the sum of two squares. In the final chapter we present some applications from Gaussian integers to trigonometry.